Time to endovascular thrombectomy for acute ischaemic stroke in language other than English (LOTE) communities in South-Western Sydney - Dennis Cordato; Peter Thomas; Alan McDougall; Cecilia Cappelen-Smith; Christopher Blair; Nathan Manning; Jing ji; Longting Lin; Mark Parsons; Andrew K Cheung; Daniel Wardman; Chushuang Chen; et al. (BMJ Neurology Open)
Background Access to endovascular thrombectomy (EVT) for acute ischaemic stroke (AIS) and the outcome disparities in culturally and linguistically diverse (CALD) populations are understudied. South-Western Sydney (SWS), characterised by high prevalence of CALD populations, provides an ideal setting to explore these disparities. This study aimed to assess whether being born in a country where English is not the primary language (‘language other than English’; LOTE) affects access to EVT and outcomes for acute ischaemic stroke while also identifying demographic risk factors influencing stroke severity and outcomes.Methods A retrospective cohort study was conducted on consecutive patients with AIS who underwent EVT at Liverpool Hospital, Sydney, from 2018 to 2023. Participants were categorised based on country-of-origin Australia/New Zealand/United Kingdom or LOTE. Primary outcomes included time metrics—onset-to-arrival (OTA) and arrival-to-puncture (ATP)—and 3-month modified Rankin Score (mRS). Statistical analyses included multivariate logistic regression to evaluate predictors of functional outcomes.Results Of 911 EVT referrals, 721 patients were included. LOTE patients (50.3%) were more likely to have diabetes mellitus (30% vs 16%; p<0.001) and presented with higher stroke severity (median National Institutes of Health Stroke Scale (NIHSS) 17 vs 14; p<0.001). They also experienced shorter ATP (158 vs 174 min; p=0.006). Patients requiring interpreters equally exhibited shorter ATP times (152 vs 170 min; p=0.01) and higher stroke severity. There was no significant disadvantage hailing from the LOTE group in OTA times and in any time metrics for subgroup analyses stratified by primary presenter status. However, LOTE patients had poorer 3-month outcomes (mRS ≤2: 46.5% vs 55.4%; p=0.021), which was associated with higher baseline NIHSS and diabetes in adjusted analyses.Conclusion LOTE patients in SWS undergoing EVT were not disadvantaged in hospital time metrics. Poorer 3-month functional outcomes in LOTE patients highlight the need for targeted strategies addressing risk factors, such as diabetes mellitus.